La construcción de la mentalidad democrática como necesidad en el posconflicto (2016)
This article, in the first instance, raises a historical tour against the armed conflict in Colombia,reaching the understanding of the causes that have generated the violence in the country.Is presented, in the second instance, a fundamental condition for the renewal of theColombian thought democratic mentality open to dialogue and discourse, as ey part of thepolitical culture to be built as an educational and illustrated process, allowing for the adventof a political pedagogy, and conflict resolution.Of the two instances mentioned political-pedagogical project of building democraticmentality as a factor that preserves democracy and jointly perform the construction of thenational state arises.In short, the article is a project proposal of building the democratic mentality in the country.